Intersectionality and Psychotherapy: Attending to Power, Privilege, and Positionality in Light of the Third - Fort, Christin J. (Journal of psychology and christianity, 2022)
The relationship between a therapist and a client is a dynamic and potentially life-changing one. Clients enter treatment hoping that therapy will help them heal and/or gain insight. Therapists hope to create the context that will make such valuable formational work possible. But, often, neither client nor therapist is aware of the ways that this transformational relationship might be impactful for the therapist as well. Attending to some of the factors that shape the bi-directional experiences of both client and therapist is the task of the present article. Specifically, attention will be paid to matters of personal identity and social location related to key concepts such as intersectionality, positionality, power, and privilege. A clinical vignette will be provided to demonstrate the ways that some of these factors might be explored in light of the psychoanalytic "Third."